(untitled) (Eurasian Journal of Philology Science and Education, 2018)
Currently in the process of teaching foreign languages, including Russian as a foreign language, an important consideration is the issue of intercultural communication. Processes and problems of intercultural communication in the literature has been reviewed in the context of international relations. Account of cultural differences, students of different nationalities, their religious affiliation, age-appropriate, characteristics of temperament, cultural traditions, native language, peculiarities of the country of residenceall this will no doubt contribute to effective learning for foreign students. Without taking into account all these features may cause problems in intercultural communication. It is important in the international audience to use communicative-significant material from the point of view of the recipient, because the content of the training will be different, depending on what kind of culture is a student.